An Evaluation on Five Dimensions of a Mobile Health Application for Patient Counseling in Ambulatory Care Pharmacy: A Single-center Cross-sectional Survey Based on Pediatric Caregiver’s Opinion - Qing-Qing Liu; Min Wang; Feng Chen; Xing Ji; Jin Xu; Zhi-Yu Wang (Journal of Research in Pharmacy Practice)
Objective: Due to high workloads and insufficient counseling time in ambulatory care pharmacy, outpatient pharmacists for pediatric patients in China proposed a mobile health application (mHealth app) that they considered could provide patient counseling more efficiently. To improve it accordingly, we need to design a more specific and multi-dimensional evaluation method to obtain pediatric caregivers’ evaluations of a mHealth app. Methods: A cross-sectional survey on five dimensions (transmission, accuracy, accessibility, completeness, and experience) of the mHealth app was conducted using a random questionnaire among outpatient caregivers at a children’s hospital. Findings: We received 478 valid questionnaires from 500 caregivers. The Item-Level Content Validity Index (I-CVI) indicated the content validity of the questions (I-CVI =1.000). The Content Validity Index for Scales (S-CVI) confirmed their content validity (S-CVI =1.000). The intraclass correlation coefficients (ICCs) of test–retest reliability were acceptable (0.806≤ ICC ≤0.869). The mean scores for transmission, accuracy, accessibility, and completeness were more than 3.5 when the experience was 2.1. Caregivers of different ages agreed that their accuracy was satisfactory; however, their experience was not. Caregivers aged over 50 years did not recognize its transmission and accessibility, whereas caregivers aged under 29 years and over 50 years were not satisfied with its completeness. Conclusion: The accuracy of the mHealth app is excellent; the transmission and accessibility need to give the silver generation time to accept and adapt, and experience and completeness should be improved. The five-dimensional assessment model can also be used to evaluate other mHealth apps for patient counseling.